PEMBERIAN IZIN BERBASIS ELEKTORINIK (ONLINE SUBMITE SISTEM) BERDASARKAN PRINSIP FIKTIF POSITIF PASCA UNDANG-UNDANG CIPTA LAPANGAN KERJA - Noor, Aslan; Prabowo, Romi Galih; Kusnadi, Engkus; Diansyah, Yogi (UNES Law Review, 2023)
Explores the concept of "fictitious positive" in the context of Indonesian administrative law, focusing on its application in public administration and licensing processes. The term refers to situations where public administration authorities fail to provide timely responses or services to citizen requests. The principle of positive fiction is enshrined in Article 53 of Law Number 30 of 2014, which sets time limits for government officials to make decisions and take actions. If the specified time limits are not met, the application is considered accepted. The State Administrative Court plays a role in adjudicating fictitious positive applications. However, recent regulatory changes introduced by the Job Creation Law have altered the process, shifting the authority to the executive branch. This abstract also examines the implementation of positive fictitious decisions in the context of the One Stop Integrated Service and the Electronic Integrated Business Licensing Service, aimed at simplifying licensing procedures and enhancing service quality. The abstract concludes by discussing the challenges and uncertainties associated with the application of positive fictitious principles in Indonesian administrative law and highlights the need for further regulations and clarity to ensure legal certainty and effective governance.